2019
DOI: 10.1021/acs.jpclett.9b01569
|View full text |Cite
|
Sign up to set email alerts
|

“Ion Solvation Spectra”: Free Energy Analysis of Solvation Structures of Multivalent Cations in Aprotic Solvents

Abstract: Using advanced molecular dynamics free energy sampling techniquesboth classical and ab initiowe analyze the solvation structures of multivalent cations in aprotic solvents. In contrast to previous studies of mono- and bivalent ions in organic solvents, mainly performed using hybrid cluster-continuum quantum chemistry calculations that rely on the assumption of uniqueness of ion solvation free energies, here we find that monatomic bivalent cations may have multiple well-defined minima, as previously reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 81 publications
2
34
0
Order By: Relevance
“…22 Several additional peaks between 1200 and 1600 cm −1 are also present in the nano-FTIR spetrum, the nature of which is still under investigation. 45,46 Interestingly, while in the case of a pure graphene membrane in contact with 0.1 M ammonium sulfate solution, the sulfate peak is about 4 times more intense than that of water, 22 the ratio near the TiO 2 film is about 2 or less. These results indicate that the structure of the electrolyte in the electrical double layer is highly influenced by the nature of the electrode and by the additional hydrogenbonding of water with O in the metal-oxide surface, which provides an anchoring and orienting mechanism for water that is very different from that in the hydrophobic graphene.…”
Section: ■ Infrared Spectroscopy Studies At the Interface Between Met...mentioning
confidence: 98%
“…22 Several additional peaks between 1200 and 1600 cm −1 are also present in the nano-FTIR spetrum, the nature of which is still under investigation. 45,46 Interestingly, while in the case of a pure graphene membrane in contact with 0.1 M ammonium sulfate solution, the sulfate peak is about 4 times more intense than that of water, 22 the ratio near the TiO 2 film is about 2 or less. These results indicate that the structure of the electrolyte in the electrical double layer is highly influenced by the nature of the electrode and by the additional hydrogenbonding of water with O in the metal-oxide surface, which provides an anchoring and orienting mechanism for water that is very different from that in the hydrophobic graphene.…”
Section: ■ Infrared Spectroscopy Studies At the Interface Between Met...mentioning
confidence: 98%
“…Standard MD protocols are however plagued by drawbacks of system size effects, starting configuration dependence, and limited sampling as compared to residence times in coordination environments that can affect the accuracy of the various ensemble averages calculated in spite of the long times that are usually used in these simulations. Recent work by Baskin and Prendergast , illustrated the use of free-energy sampling methods like umbrella sampling , and metadynamics , in the framework of both classical and ab initio MD to overcome some of these deficiencies and gain more rigorous insight into ion solvation environments.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that the redox stability of solvent molecules is affected by the molecular‐level interactions within an electrochemical system, such as between the cations, anions, other solvent molecules, and the electrode surface. [ 34–36 ] The ability to renormalize the highest occupied molecular orbital (HOMO) level of solvent molecules provides a good indication of oxidative stability. Interactions with anions destabilize the HOMO state, thereby promoting oxidation, while interactions with cations stabilize the HOMO state and hinder oxidation (Figure 4b).…”
Section: Resultsmentioning
confidence: 99%